Comparison of on-water rowing with its simulation on concept2 and rowperfect machines - Kleshnev , V. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
The purpose of this study was to identify biomechanical differences and similarities between on-water rowing and its simulation on Concept2 and RowPerfect rowing machines. Handle force, positions of the handle, seat and trunk, shell acceleration were measured in single scull and on both machines in five female rowers. It was found that the rowers applied 30% - 40% higher handle force on both machines than on-water. Stroke length was 11%-12% shorter on both machines, which mainly occurred by means of 30% shorter arms drive. Legs drive was 4% - 6% longer on Concept ergo-meter than on both RowPerfect and on-water. Significant differences were found in the handle velocity and shell acceleration profiles. Machines should be considered as a cross-training for rowers and can not replace on-water rowing.